PEDAGOGICAL CULTURAL DIRECTIONS IN THE EXAMPLES OF UZBEKISTAN AND GREAT BRITAIN COUNTRIES - Ernazarova Zulkhumor Muhammadi qizi (PEDAGOGS, 2024)
Abstract. This article provides information about the opportunities and directions of pedagogical culture in Uzbekistan and Great Britain. The article also shows the psychological-pedagogical features and components of the development of the professional culture of school teachers